2022
DOI: 10.1109/tmag.2022.3178489
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Circulating Currents in Parallel Foil Windings for Medium Frequency Transformers

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…while 𝑣 𝑐 is the total volume of the core, and the specified material properties used in (7) are given in Table . 2.…”
Section: B Core Lossmentioning
confidence: 99%
See 3 more Smart Citations
“…while 𝑣 𝑐 is the total volume of the core, and the specified material properties used in (7) are given in Table . 2.…”
Section: B Core Lossmentioning
confidence: 99%
“…However, the circulating currents between asymmetrical parallel-wound foil winding can cause multiple times higher loss inside the windings. In [7], we investigated the presence of circulating currents in parallelwound MFTs. The study showed high ratio of phase and S. Pourkeivannour, M. Curti, and E. A. Lomonova are with Eindhoven Technical University, Electrical Engineering Department, Eindhoven, the Netherlands (e-mail: s.pourkeivannour@ieee.org).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The price for these advantages is the use of more complex and therefore more expensive conductors and core materials to keep the frequencyinduced losses in an acceptable range. In this respect, the conductor choice is constrained among foil or litz wire, e.g., [11]- [14]: litz wire is disfavored by the reduced filling factor, the limited availability and the elevated cost, whereas foil conductor exhibits additional ohmic losses due to the so-called "current crowding" or edge effect, caused by the deformation of the magnetic field due to the insulation clearance to the core [15]. Foil windings exhibit a uniform voltage distribution in the case of steepfronted PWM voltages [16], which is advantageous for MV SST applications; however, the electric field hotspots at the foil winding corners limit the insulation rating [17].…”
Section: Introductionmentioning
confidence: 99%